PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS KONSTRUKTIVISME UNTUK MATERI GEOMETRI SMP - Nur Alfajri (Jurnal Edukasi dan Penelitian Matematika, 2019)
Interactive learning multimedia is a supporting tool in the learning process,so that it is more interesting and helps visualize topics that is still abstract. One of the topics is on the material solid figure. The purpose of this study was to develop constructivism based interactive learning multimedia for material of a solid fgure that was valid and practical. The type of research was a development research used Plomp model consisting of the preliminary research phase and prototyping phase. The Preliminary research phase includes needs analysis, student analysis, curriculum analysis and concept analysis. Prototyping phase was the stage of design interactive learning multimedia consisting of prototype 1, prototype 2, prototype 3 and prototype 4 which were evaluated using a formative evaluation design. The results of this study show that the interactive learning multimedia produce is valid and practical.Keywords – Constructivism, Geometry, Interactive learning multimedia, Plomp